Hypocoristic and Anthroponyms in songs by “Chava Flores” - Gutiérrez Santana, Lucila (Interpretextos revista semestral de creación y divulgación de las humanidades (Colima), 2025)
Salvador Flores Rivera (Chava Flores) was an important Mexican singer and composer, famous in the mid-20th century, known as a chronicler of the neighborhood for his festive style and use of popular vocabulary. In his lyrics, we can identify the use of hypocoristics (affectionate shortenings of proper names) and anthroponyms (personal names) characteristic of the then-called Federal District. The hypocoristics present in Chava Flores’ songs include minimal Spanish words, disyllabic or bimoraitic, with a grave accent and preferably light and open syllables. Some anthroponyms are part of the Mexican Catholic tradition, taken from the calendar of saints, or invented by the author.